2017
DOI: 10.1021/acs.energyfuels.7b00194
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Catalytic Glycerol Etherification with Ethanol in a Continuous Reactor

Abstract: In the past few decades, biodiesel has emerged as a promising renewable energy source. However, its production usually leads to the formation of large amounts of glycerol as a byproduct. This article reports the evaluation of catalytic glycerol etherification with ethanol over a series of catalysts in a continuous reactor. Amberlyst 15 presented the best performance in terms of glycerol conversion and yield of ethers. This result was attributed to its high pore size and acidity. Beta zeolite (Si/Al = 12.5) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
0
9
0
10
Order By: Relevance
“…Glycerol etherification in the presence of ethanol with acidic resin was studied in a continuous flow reactor to obtain 1-O-ethylglycerol. 57 Among the three commercial heterogeneous acid catalysts used, Amberlyst 15, β-zeolite, and niobic acid, the strong acid ion-exchange resin led to better conversion and yield of ethers. This study found that the most significant factor in the conversion of glycerol was the amount of catalyst, followed by temperature, and then molar ratio.…”
Section: Continuous Etherificationmentioning
confidence: 99%
“…Glycerol etherification in the presence of ethanol with acidic resin was studied in a continuous flow reactor to obtain 1-O-ethylglycerol. 57 Among the three commercial heterogeneous acid catalysts used, Amberlyst 15, β-zeolite, and niobic acid, the strong acid ion-exchange resin led to better conversion and yield of ethers. This study found that the most significant factor in the conversion of glycerol was the amount of catalyst, followed by temperature, and then molar ratio.…”
Section: Continuous Etherificationmentioning
confidence: 99%
“…Nosso grupo de pesquisa (Lemos et al, 2018a;Lemos et al, 2017) investigou a eterificação do glicerol com etanol em reator contínuo e com um tempo de residência em torno de 60 s. No trabalho desenvolvido à pressão atmosférica (Lemos et al, 2017), com temperaturas variando de 160 a 210 °C, razão molar etanol/glicerol de 4:1 a 16:1 e Amberlyst 15 de 0 a 0,80 g, os valores ótimos para conversão e rendimento de glicerol para éteres foram 91% e 13%, respectivamente. No entanto, à pressão atmosférica, a mistura de reação está em duas fases.…”
Section: 211a Eterificação Com áLcooisunclassified
“…Então, na posse desses resultados, nosso grupo de pesquisa realizou um novo estudo com pressão fixa de 8,5 MPa (Lemos et al, 2018a). Neste trabalho, eles mantiveram a variação da quantidade de Amberlyst e da razão molar etanol/glicerol conforme descrito acima (Lemos et al, 2017), mas as temperaturas variaram de 180 a 250 °C. Os valores ótimos foram 97% da conversão de glicerol (a 268 °C, etanol/razão molar de glicerol de 24,20/1 e 0,76 g de catalisador) e 56% de rendimento de éteres (a 238 °C, razão molar etanol/glicerol de 16/1 e 0,61 g de catalisador).…”
Section: 211a Eterificação Com áLcooisunclassified
See 1 more Smart Citation
“…Entretanto, da mesma forma como observado na curva de "light-off" da Amberlyst 15 testada sem pressão, o maior valor de rendimento (41%) não se deu na mais alta temperatura. Este comportamento pode ser atribuído formação de compostos indesejáveis, tais como acroleína e éter dietílico, os quais são favorecidos em altas temperaturas(LEMOS et al, 2017;KLEPAKOVA et al, 2005. A zeólita beta atingiu aconversão máxima de 54% e rendimento de 33% a 250 °C.…”
unclassified